Marine Water Quality at Diego Garcia: A Preliminary Study of Pollution Levels in Coastal and Lagoon Waters - Painting, Suzanne J.; Nelson, Paul; Smith, Andy J.; Graves, Carolyn A.; Powell, Andy; Bersuder, Philippe; Bullen, Samuel; Archer-Rand, Simeon (Frontiers in Marine Science, 2021)
Diego Garcia is the largest atoll within the Chagos Archipelago in the Indian Ocean. Since the 1960s it has been a military base, populated only by military and support personnel. Infrastructure includes sewage treatment works, a waste disposal facility and an airbase. Lagoon use includes boating and large vessel anchorage. Current pollution levels by inorganic nutrients and other contaminants are unknown. A field study was undertaken in March 2019 to obtain baseline information on key environmental parameters and pollutants for assessing the state of marine water quality. Outside the atoll, three stations were sampled where human impacts were likely to be lowest (two off the north coast, considered as ‘near-pristine’; one on the east coast); one station was sampled in the lagoon mouth; 10 stations were sampled downstream from two sewage outflows. Inside the lagoon, 10 stations were sampled at near-shore sites likely to be directly impacted by activities such as boating and waste management; six stations were sampled in the central or eastern lagoon. In situ sensors were used to estimate temperature, salinity, chlorophyll (as fluorescence) and dissolved oxygen. Discrete water samples were analysed for nutrients, chemical contaminants, heavy metals and faecal indicator bacteria. Sea surface temperatures were highest (29.5 - 35 oC) inside the lagoon; salinities were generally higher (>34.1) outside the lagoon (vs 33.8-34.1 inside). Surface nutrient concentrations at near-pristine stations were undetectable for nitrate and phosphate and averaged 1.39 µM for dissolved inorganic nitrogen (DIN) and 1.73 µM for silicate. Concentrations were higher at most other stations (maximum 5.7 µM DIN, 0.38 µM phosphate, 9.93 µM silicate), with ammonium contributing most to DIN. In the lagoon, chlorophyll concentrations were relatively low (0.3 - 0.6 µg chl l-1) near the surface and higher (max 0.9 µg chl l-1) at depth. Results suggested low levels of pollution overall. However, levels of nutrients, oxygen deficiency, chemical contaminants (e.g. solvents and DEET) and heavy metals (cadmium, nickel, zinc and copper) at some sites inside the lagoon are a concern due to slow flushing rates and will be used to inform future monitoring and assessment of environmental health at Diego Garcia.